Structural and elastic properties of xCaO-10PbO-(90-x)B2O3 glass system / Nur Farhah Mahmud - Mahmud, Nur Farhah (2020)
This study investigate the structural and elastic properties glass system of xCaO-10PbO-(90-x)B2O3 with composition (x = 20, 25, 30, 35 and 40) by using melt-quenching method. The structural of the glass system is determined by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. FTIR analysis showed the functional group of BOB, B04 and B03 in specific range. Meanwhile, for elastic properties are determined by using pulse-echo method which also known as ultrasonic measurement. Ultrasonic measurement used in order to obtain longitudinal and shear velocities for each glass samples. By adding CaO content into borate-lead glass system, it will increase the elastic moduli (Ke and CL) for x ≤ 35 mol% and later decreasing at x > 35 mol%.